Research with undocumented migrant participants - Cancino-Jiménez, Daniella; Leyva Flores, René; Valencia-Contrera, Miguel; Cancino-Jiménez, Jorge; Febré, Naldy (Revista Cuidarte, 2024)
Highlights • Migration has significant implications for public health, making it imperative to continue research efforts to develop and deliver coherent and culturally appropriate responses. • Nursing science is relevant in this area primarily because it seeks to provide guidance on ethical aspects concerning migrant populations. • The ethical knowledge within nursing science offers models and theories that guide both clinical practice and research. • We consider it relevant to understand and explore alternatives based on principles and values, fostering critical thinking in nursing actions. Globally, migration is increasing at an accelerated and sustained rate, driven by social, political, and economic factors that prompt the displacement of people across countries, resulting in significant migratory waves1-4. It is estimated that there are 272 million international migrants worldwide3. Migration is defined by the International Organization for Migration (IOM) as the “Movement of persons away from their place of usual residence, either across an international border or within a State”5. How to cite this article: Cancino-Jiménez Daniella, Leyva Flores René, Valencia-Contrera Miguel, Cancino-Jiménez Jorge, Febré Naldy. Research with undocumented migrant participants. Revista Cuidarte. 2025;16(1): e4621. https://doi.org/10.15649/cuidarte.4621